2021
DOI: 10.2144/fsoa-2021-0020
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Pillar Implants to Reduce Snoring and Daytime Sleepiness

Abstract: Objective: To measure the efficacy of pillar implants in reducing snoring. Materials and methods: A total of 30 adult patients who underwent pillar implants were assessed preoperatively and at 1, 3, 6 and 12 months after the implantation. Improvement was measured using snoring frequency, visual analog scale for snoring loudness, and Epworth sleepiness scale for daytime sleepiness. Results: The mean snoring frequency, loudness and Epworth score were reduced from 6.9, 9.2 and 7.4 at the baseline to 5, 5.9 and 5.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 69 publications
0
1
0
Order By: Relevance
“…[7][8][9] Based on the significant impact of daytime sleepiness on an individual's physical and mental health and wellbeing, there has been increasing concern about daytime sleepiness. Most studies on daytime sleepiness have focused on populations with sleep-related breathing disorders 2,10,11 or those secondary to somatic and psychiatric disorders. [12][13][14][15] Several studies have also shown a high prevalence of daytime sleepiness, poor sleep quality, and poor sleep health among medical students, 9,16 nurses, 17 and the general population.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9] Based on the significant impact of daytime sleepiness on an individual's physical and mental health and wellbeing, there has been increasing concern about daytime sleepiness. Most studies on daytime sleepiness have focused on populations with sleep-related breathing disorders 2,10,11 or those secondary to somatic and psychiatric disorders. [12][13][14][15] Several studies have also shown a high prevalence of daytime sleepiness, poor sleep quality, and poor sleep health among medical students, 9,16 nurses, 17 and the general population.…”
Section: Introductionmentioning
confidence: 99%